Prolonged Cardiac Monitoring for Atrial Fibrillation Detection After Stroke: In Search of the Elusive Sweet Spot. (10th May 2022) - Sposato, Luciano A.; Andrade, Jason
Abstract : Prolonged cardiac monitoring (PCM) is one of the pillars of the diagnostic workup for patients with ischemic stroke. However, the ideal duration of PCM for atrial fibrillation (AF) detection after stroke has not been established. Recommendations on PCM duration after stroke vary across clinical guidelines from nonspecific long-term monitoring 1 to 2 weeks. 2 Furthermore, AF screening strategies after stroke vary widely in clinical practice, 3, 4 possibly due to differences in access to monitoring technologies, 4 vague recommendations from clinical guidelines, 1 and lack of data supporting a specific duration of monitoring.